Proteomic analysis of murine bone marrow derived dendritic cells in response to peste des petits ruminants virus. (August 2019) - Li, Lingxia; Wu, Jinyan; Cao, Xiao''an; Zhou, Jianhua; Yin, Shuanghui; Yang, Shunli; Feng, Qian; Du, Ping; Liu, Yongjie; Shang, Youjun; Liu, Yongsheng; Liu, Xiangtao
Abstract: Peste des petits ruminants virus (PPRV) poses a great threat to livestock husbandry, especially goat farming due to its high mortality and morbidity. Dendritic cells (DCs), as the principal stimulators of naive Th cells were widely used in antigen processing and presenting. In the previous study, we tested the effects of PPRV on murine bone marrow derived dendritic cells (BMDCs) including surface markers and cytokines. While the aim of this study is to detect the proteomic profile of BMDCs stimulated with PPRV towards key proteins involved in. Following PPRV stimulation, 110 differentially expressed proteins (DEPs) were identified through iTRAQ labelling with LC–MS/MS approach, of which 94 DEPs were up-regulated and 16 DEPs were down-regulated, respectively. Among them 15 out of 110 DGPs were related to innate immune system, three were involved in cell apoptosis, RPS15a and Smox were related to translation of viral mRNA. Additionally, western blot analysis showed identical results to iTRAQ analysis. There will be profound significance for understanding antigen-presenting of BMDCs after stimulation with PPRV. Highlights: PPRV could produce an immune response to BMDCs during PPRV stimulation. Responses of BMDCs to PPRV were investigated using proteomics analysis. Our data therefore provide immunosuppression insights into the infection of PPRV. That provide a comprehensive insight into the cellular response of BMDCs to PPRV.